A Game Analysis on Information Sharing of Military Procurement and Logistics Standardization - Ling Darong; Zhang Fei; Wang Ziyi; Li Yukun (MATEC Web of Conferences, 2017)
Military procurement and logistics standardization is the base of the efficient and reasonable operation of modern military procurement &logistics. It's significant to study logistics standardization and the standardization of logistics information management. This paper constructs a game model which aims at comparing costs and benefits on condition of absolute sharing, partial sharing or not sharing information based on the different information sharing rate and logistics institutes’ expectation, furthermore, it discusses how to build a relationship of mutual trust, in order to make the logistics institutes develop activeness to fasten the pace of logistics standardization and the standardization of logistics information management.